Correlation between the automated slump test and the rheological properties of Portland cement mortars - Pereira, João Batista [UNESP]; de Freitas Maciel, Geraldo [UNESP] (Emerald, 2024)
The aim of this work was to conduct a rheological assessment of mortars based on the automated slump test. Using this test to monitor the transient and permanent regime of slump and its spread, the parameters were correlated with the rheological properties of the mortars. Based on dimensionless slump/spread, yield stress and viscosity, empirical models were developed for obtaining rheological parameters, which provided correlations with good coefficients of determination (R2 > 0.85). Through analysis of the slump behaviour of the mortars, a correlation between the viscosity and the maximum slump velocity was obtained (R2 = 0.90), showing that viscosity could be determined based on the slump velocity. Furthermore, based on a physical description of the slump test related to the Reynolds number, three distinct stages in the slump process were defined: the viscous phase (characterised by high viscosities), the intermediate phase (the coexistence of viscous and inertial effects) and the inertial phase (characterised by low viscosities and a higher sensitivity to lifting of the mould). The dynamic similarity of the analysed mortars (vertical Reynolds number/radial Reynolds approximately equal to one) indicated that the shear rate could be measured based on the vertical direction of the flow (slump).
Keywords: empirical models; mortar; slump test; viscosity; yield stress